Effect of repetitive sub-concussive head impacts on ocular near point of convergence - Kawata, K.; Tierney, R.; Phillips, J.; Jeka, J. J. (International Journal of Sports Medicine, 2016)
This study intended to examine effects of repetitive sub-concussive head impacts on ocular near point of convergence (NPC). 20 healthy young adult soccer players were assigned to either a heading or control group. Heading subjects completed 10 headers of soccer balls projected at a speed of 11.2 m/s. Control subjects did not perform heading. Linear head acceleration was measured with a triaxial accelerometer. The NPC assessment was performed at pre-, 0 h post-, and 24 h post-heading. During the NPC assessment participants were seated and a visual target was moved towards the eyes at 1cm/sec. The participant signaled when he/she experienced diplopia or deviation of the eye was observed, and the distance was recorded. The assessment was repeated twice and average NPC scores were used for further analysis. Soccer heading induced mean group head accelerations of 14.49±5.4 g. Mild head impacts led to an increased NPC distance, which was supported by a significant Group x Time interaction. In the heading group, 0 h post- and 24 h post-heading NPC scores were significantly receded compared to baseline. Conversely, NPC scores for the control group showed no difference over time. Our findings indicate that mild frontal head impacts affekt NPC for a minimum of 24 h-post heading, suggesting that oculomotor processes are disrupted, at least transiently, by repetitive mild head impact.